Partnership model of vocational education with the business sector in civil engineering expertise program of Vocational Secondary Schools - I Kadek Budi Sandika; Slamet Slamet; Husaini Usman (Jurnal Pendidikan Vokasi, 2017)
This study aims to: (1) develop a partnership model of vocational education with business sectors in civil engineering expertise program of vocational secondary schools in Bali and (2)testing the effectiveness and efficiency of partnership model developed. The study used the design and development model of Richey & Klein (2009), which consists of three main phases, namely the phase of model development, model validation, and model testing. The phase of model development used the qualitative approach, through literature review, observation and interview. Expert review techniques were used in the model validation phase. The model testing used pre-experimental design with one-shot case study. The study found that the partnership model of vocational education with the business sector in civil engineering expertise program of vocational secondary schools in Bali involves several components, such as key stakeholders, the underlying principle of partnership, orientation/common goal, the management of educational resources (teachers and facilities), curriculum development, implementation of learning/training and work practices, competency test of graduates, distribution of learning outcomes/output, as well as monitoring, evaluation and feedback of partnership program. Experimental results show that the partnership model developed has met all of the criteria (effective, practical and efficient).